A case report of lumbosacral plexopathy in a patient with a history of sacral chordoma and radiotherapy: Will the detection of myokymia on the EMG help to solve the case? - ALBAYRAK, OSMAN; KENİŞ COŞKUN, ÖZGE; YAĞCI, İLKER; GÜNDÜZ, OSMAN HAKAN (My University, 2023)
BACKGROUND: When a patient with a prior history of malignancy and radiotherapy develops progressive weakness as a presentation of plexus involvement, the differential diagnosis usually rests between radiation-induced plexopathy and invasion from recurrent tumor. The presence of myokymic discharges is helpful in differentiating radiation-induced from neoplastic plexopathy.
Keywords: Tıp; Dahili Tıp Bilimleri; Fiziksel Tıp ve Rehabilitasyon; Cerrahi Tıp Bilimleri; Ortopedi ve Travmatoloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Physical Medicine and Rehabilitation; Surgery Medicine Sciences; Orthopedics and Traumatology; Health Sciences; ORTOPEDİ; Klinik Tıp; Klinik Tıp (MED); REHABİLİTASYON; ORTHOPEDICS; CLINICAL MEDICINE; Clinical Medicine (MED); REHABILITATION; Ayak Bakımı; Fizik Tedavi, Spor Terapisi ve Rehabilitasyon; Kayropraktik; Rehabilitasyon; Ortopedi ve Spor Hekimliği; Podiatry; Physical Therapy, Sports Therapy and Rehabilitation; Chiropractics; Rehabilitation; Orthopedics and Sports Medicine; Case report; chordoma; electromyography; lumbosacral plexopathy; myokymia; radiation; CANCER